2013
DOI: 10.1186/1897-4287-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenesis of PIK3CA

Abstract: PIK3CA is the most frequently mutated oncogene in human cancers. PIK3CA is phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha. It controls cell growth, proliferation, motility, survival, differentiation and intracellular trafficking. In most of human cancer alteration occurred frequently in the alpha isoform of phosphatidylinositol 3 kinase. PIK3CA mutations were most frequent in endometrial, ovarian, colorectal, breast, cervical, squamous cell cancer of the head and neck, chondroma, thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…These agents are currently being tested in clinical trials, both as single agents and in combination with other treatments [30,35] (Table 3).…”
Section: The Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…These agents are currently being tested in clinical trials, both as single agents and in combination with other treatments [30,35] (Table 3).…”
Section: The Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…Numerous mutations or alterations in the PI3K pathway have now been identified in human SCCHN, at the level of both gene expression and function (Table 2) [29]. These genes include, but are not limited to: PIK3CA, PIK3CD, PTEN, PDK1, AKT, and mTOR [8,[30][31][32][33][34][35]. Mutations and copy number alterations of PI3K pathway components, including PIK3CA amplifications and PTEN inactivation by loss or inactivation of gene copy, are particularly prevalent in HPV-positive tumors [36].…”
Section: The Pi3k/akt/mtor Pathwaymentioning
confidence: 99%
“…These ligands include epidermal growth factor (EGF) or VEGF. Somatic mutations in cancer cells only occur in PIK3CA and PI3KR1, which encodes the p85 α subunit (3,6,9). These mutations are concentrated in two key regions of the PIK3CA gene, consisting of the helical domain of exon 9 and the kinase domain of exon 20 (7,8,10).…”
Section: Introductionmentioning
confidence: 99%
“…EGFR triggers a downstream signalling cascade through, for example, the Kirsten rat sarcoma viral oncogene homolog-serine/threonine-protein kinase B-Raf and the phosphatidylinositol 3-kinase (PI3K), catalytic subunit α-phosphatase and tensin homolog-Akt pathways, which regulate cell proliferation, survival, apoptosis resistance, invasion and migration (2,3,(5)(6)(7)(8). The PIK3CA gene encodes the p110α subunit of PI3K α and belongs to class IA of the PI3Ks.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Carnero A et al 2008 have indicated that a class of HDAC protein SIRT1 is required for PI3K mediated cancer cell growth. 5,6 PI3K/Akt /mTOR signaling can reduce p53 response through inhibitory effect on its stability. 7 Tumor suppressor gene p53 plays a crucial role in executing anti-proliferative effects such as growth arrest, apoptosis and cell senescence, in response to various types of stress.…”
Section: Introductionmentioning
confidence: 99%